Pemberian Biochar Jengkok Tembakau untuk Meningkatkan Hasil Ubijalar pada Lahan Kering Sub-Optimal - Edyson Indawan; Sri Umi Lestari; Nurita Thiasari (Jurnal Lahan Suboptimal : Journal of Suboptimal Lands, 2019)
Indawan et al, 2019. Increasing Sweet Potato Yield on Biochar Amendment Application on Sub-Optimal Dry Land. JLSO 8(1):47-56. Biochar is a soil amendment that can improve soil fertility, increase crop yield and can reduce contamination. This study aim to evaluate the sweet potato response to biochar application from tobacco industry waste. The combination of cultivar and dose of biochar implemented using a Split Plot Experiment Design with three replications. The cultivars placed 0n main plots and biochar doses on sub-plots. The thirteen cultivars covering 7 varieties (Kuningan Putih, Beta 1, Beta 2, Kuningan Merah, Sari, Boko, and Jago) plus six accession from Unitri and Brawijaya University collections (BIS OP-61-OP-22 , 73-6 / 2, 73 OP-8, BIS OP-61, 73 OP-5, and BIS OP-61-♀-29). The biochar dose used was B0 (0 t / ha) and B1 (5 t / ha). The experimental unit is measuring 5 m x 0.6 m, consisting of single row and planted with a spacing of 25 cm in row or 20 cuttings/row). The storage root numbers, storage root weight, % dry matter, Harvest Index (HI) and yields estimation are ditermined. The results showed that sweet potato cultivars gave a significant response to biochar application on fresh storage root weight, dry storage root weight, biomass dry weight, HI and storage root yields, but no interaction between cultivars and biochar doses. Storage root yield range of 8 - 21 t / ha without biochar and 10 - 23 t / ha with biochar 5 t / ha, except for Beta 1 and Boko. The use of biochar of 5 t / ha can increase storage root yields ranging from 8 - 45%.